Evolution of the parent body of enstatite (EL) chondrites - Trieloff, Mario; Hopp, Jens; Gail, Hans-Peter (Icarus, 2022)
Chondrites stem from undifferentiated asteroidal parent bodies that nevertheless experienced a certain degree of metamorphism after their formation in the early solar system. Maximum temperatures of metamorphism depend mainly on formation time and the abundance of the main heating source, which is short-lived 26Al (half life 720 000 yr). Enstatite chondrites formed under reducing conditions and include many strongly metamorphosed members of petrologic type 6. We model the thermal evolution of the parent body of the low metal enstatite chondrite class (EL). The model takes into account accretion, heating, sintering and compaction by hot pressing of the initially porous material, temperature dependent heat conductivity, and insulation effects by the remaining regolith layer. A fit of key parameters of the parent body comprising formation time, radius, and porosity is achieved by fitting thermal histories of EL6 chondrites (LON 94100, Neuschwanstein, Khairpur, Blithfield, Daniel’s Kuil) constrained mainly by I-Xe and Ar-Ar ages and their respective closure temperatures. Viable fits are obtained for parent bodies with 120-210 km radius, formed c. 1.8-2.1 Ma after Ca,Al rich inclusions (CAIs), and an initial porosity of 30%, relatively independent on initial disk temperatures. Optimised models with parent body formation-times >1.95 Ma after CAIs imply central core temperatures below incipient plagioclase silicate melting. Thermal histories of the different EL6 chondrites are indistinguishable and so are their burial depths. While the exact layering depth is somewhat model dependent (c. 12-20 km), the thickness of the layer from which all five EL6 chondrites stem is <1 km. Hence, an origin from a quite small asteroidal fragment is possible, particular as most excavation ages inferred from cosmic ray exposure data are compatible with a separation as metre sized meteoroids from a small Apollo asteroid 33 Ma ago.
Available online 30 October 2021
Gesehen am 17.12.2021